ANALISIS PEMAHAMAN MAHASISWA MATEMATIKA TERHADAP KONSEP DASAR GEOMETRI EUCLID DITINJAU DARI UNSUR DASAR, AKSIOMA, POSTULAT, DAN PROPOSISI - Riris Irawati Sinurat; Dea Ananda Claudia Nainggolan; Fanden Batara Damanik; KMS Muhammad Amin Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze mathematics education students’ understanding of the basic concepts of Euclidean geometry in terms of its basic elements, axioms, postulates, and propositions. A descriptive quantitative approach was used with 42 students from the University of Medan who had taken the Euclidean Geometry course as subjects. The instrument consisted of a 10-item multiple-choice test measuring six indicators. The data were analyzed descriptively. The results showed an average score of 84.76 (Very Good category). Fifty percent of the students fell into the Very Good category and 50% into the Good category; no students were in the Fair, Poor, or Very Poor categories. The score distribution was not normal (Shapiro-Wilk p<0.05) with a sample standard deviation of 11.31. Preliminary analysis of the indicators revealed very good understanding of basic elements, postulates, and simple proofs, but weak performance in the application of concepts (only 39.13% correct) and the concept of axiomatic independence (52.17% correct). Although the overall results appear high, weaknesses in applied reasoning and axiomatic structure still need to be addressed. The study recommends strengthening the teaching of deductive reasoning and providing practice in applying theorems in non-routine contexts